Les alpinistes et les limites terrestres du vivant : une contribution atypique à la connaissance scientifique - Cédric Dentant; Pascal Mao; Sébastien Lavergne; Philippe Bourdeau. (Revue de Géographie Alpine)
High mountain environments have long been considered to be devoid of life. If science has been a relevant means of legitimization and narrative from the very first explorations of high altitudes, life sciences (biology, ecology) have occupied only a marginal place. Even the inventor of biogeography, Alexander von Humboldt, saw little interest in studying these margins of the biosphere. However, the pioneers of alpinism have approached these terra incognita beyond the sole prism of the geographical unknown. Personalities such as Edward Whymper perceived that the involvement of their bodies in these extreme environments could be a powerful means of producing knowledge, through the collection of unsuspected living organisms, and by extension to become contributors to science. Professional scientists had to take hold of these intermediate objects, and make themselves mediators between the field and theory; they had to become « mediating beings ». Until the emergence of a new scientific assemblage, involving new actors from conservation biology. Mountaineers have thus mutated from collector bodies to co-producers of science.